Pelaksanaan Pencegahan Covid 19 di Masyarakat Kelurahan Talang Banjar Kota Jambi - Iin Indrawati; Faridah Faridah (Universitas Baiturrahim, 2022)
Covid-19 cases in Indonesia in early June 2022 were reported to increase by 551 cases The purpose of the study was to describe the implementation of Covid-19 prevention in the Talang Banjar Village Community, Jambi City. This research is a quantitative research using a descriptive analytic design. The population and sample in this study were the people of Talang Banjar Village, Jambi City who took part in weekly gymnastics at the Talang Banjar Village Head Office, Jambi City, amounting to 30 people. Sampling was done by using total sampling technique. The implementation of Covid-19 prevention in the Talang Banjar Village community can be seen from how the public's perception of the Covid-19 disease and their behavior in preventing Covid-19 is in accordance with the health protocol imposed by the government. The perception of the Talang Banjar village community about Covid-19 is mostly good, namely 86.7% and community behavior according to health protocols in preventing the transmission of the Covid-19 virus is mostly good, namely 82.8%. The government's program to prevent the spread of the Covid-19 virus is to invite people to live healthy lives through habits to comply with health protocols that have been established and health workers must more often and make regular plans to always provide health education to the community to be able to educate the nation